2021
DOI: 10.1177/23259671211031652
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Testing of 2 Adjustable-Loop Cortical Suspensory Fixation Systems Versus Interference Screw for Anterior Cruciate Ligament Reconstruction

Abstract: Background: It is not clear whether the mechanical strength of adjustable-loop suspension devices (ALDs) in anterior cruciate ligament (ACL) reconstruction is device dependent and if these constructs are different from those of an interference screw. Purpose: To compare the biomechanical differences of 2 types of ALDs versus an interference screw. Study Design: Controlled laboratory study. Methods: ACL reconstruction was performed on porcine femurs and bovine extensor tendons with 3 types of fixation devices: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…The anatomy of porcine knees was shown to be sufficiently similar to that of human knees, 46 and porcine flexor tendons possess biomechanical properties similar to those of human hamstring tendons, 17 making it a frequently used model to assess the biomechanical primary stability of orthopaedic implants. 19,23,24,43 Nevertheless, bone density in the porcine model is significantly higher in comparison with humans, 1 which could have affected the findings of the present study. 8,42 A recent study showed that, in a test setup like that used in this study, the displacement of the machine actuator used to calculate the elongation was significantly higher than the actual graft slippage, as measured by optical tracking at the tunnel aperture, although both values were highly correlated.…”
Section: Limitationsmentioning
confidence: 68%
“…The anatomy of porcine knees was shown to be sufficiently similar to that of human knees, 46 and porcine flexor tendons possess biomechanical properties similar to those of human hamstring tendons, 17 making it a frequently used model to assess the biomechanical primary stability of orthopaedic implants. 19,23,24,43 Nevertheless, bone density in the porcine model is significantly higher in comparison with humans, 1 which could have affected the findings of the present study. 8,42 A recent study showed that, in a test setup like that used in this study, the displacement of the machine actuator used to calculate the elongation was significantly higher than the actual graft slippage, as measured by optical tracking at the tunnel aperture, although both values were highly correlated.…”
Section: Limitationsmentioning
confidence: 68%
“… 20 , 36 , 41 First, isolated testing of the implant led to lower elongation and higher load to failure in comparison to in vitro ACLR. 6 , 12 , 19 , 24 , 36 However, the influence of the interface between the implant and the cortical bone or the tendon graft is not considered in isolated implant testing. Second, in numerous biomechanical studies, cyclic loading was performed without complete unloading.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we modified the LHBT fixation technique to the adjustable loop suspensory system, which allowed enough tendon-to-bone contact inside the glenoid tunnel and provided greater mechanical strength. 30…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we modified the LHBT fixation technique to the adjustable loop suspensory system, which allowed enough tendon-tobone contact inside the glenoid tunnel and provided greater mechanical strength. 30 Bone resorption during the graft remodeling phase weakens the bone-mediated biomechanical effect on anterior shoulder stability, especially with allografts. 57,60 In 2 recent studies using iliac crest bone allografts, Boehm et al 9 reported nearly complete bone resorption in all patients with only a 2.2% glenoid defect decrease at 1year follow-up, Russo et al 56 observed that 10 of 19 patients had complete bone resorption.…”
Section: Discussionmentioning
confidence: 99%